2017
DOI: 10.1073/pnas.1706267114
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation determines the voltage required to activate cardiac I Ks channels

Abstract: I Ks channels open in response to depolarization of the membrane voltage during the cardiac action potential, passing potassium ions outward to repolarize ventricular myocytes and end each beat. Here, we show that the voltage required to activate I Ks channels depends on their covalent modification by small ubiquitin-like modifier (SUMO) proteins. I Ks channels are comprised of four KCNQ1 poreforming subunits, two KCNE1 accessory subunits, and up to four SUMOs, one on Lys 424 of each KCNQ1 subunit. Each SUMO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…We delivered 1 nM purified SUMO1 peptide into iPS-CMs by the patch pipette; a concentration that evoked maximal effects on Na V 1.2 channels in cerebellar granule neurons (CGNs) and three different K + channels in CGNs, hippocampal neurons, and rat cardiac myocytes (Xiong et al, 2017;Plant et al, 2011Plant et al, , 2012Plant et al, , 2016. SUMO1 induced changes in cardiac I Na like those produced by hypoxia: I LATE increased to $4.2% of peak I Na without a change in the peak magnitude ( Figures 1B and 1C; Table 1).…”
Section: Sumo1 Increases I Late In Human Ips-cmsmentioning
confidence: 99%
See 1 more Smart Citation
“…We delivered 1 nM purified SUMO1 peptide into iPS-CMs by the patch pipette; a concentration that evoked maximal effects on Na V 1.2 channels in cerebellar granule neurons (CGNs) and three different K + channels in CGNs, hippocampal neurons, and rat cardiac myocytes (Xiong et al, 2017;Plant et al, 2011Plant et al, , 2012Plant et al, , 2016. SUMO1 induced changes in cardiac I Na like those produced by hypoxia: I LATE increased to $4.2% of peak I Na without a change in the peak magnitude ( Figures 1B and 1C; Table 1).…”
Section: Sumo1 Increases I Late In Human Ips-cmsmentioning
confidence: 99%
“…SUMOylation is the enzyme-mediated linkage of one of three SUMO isoforms to the ε amino group of specific lysine residues in a target protein (Henley et al, 2014). Present in all eukaryotic cells, the SUMO pathway was known to regulate the trafficking and activity of nuclear transcription factors when we described it to operate as well at the plasma membrane by direct SUMOylation of Na + and K + channels to regulate excitability Plant et al, 2010Plant et al, , 2011Plant et al, , 2012Plant et al, , 2016Xiong et al, 2017). Given the important role of hypoxia-induced increases in I LATE in heart disease, we tested the hypothesis that SUMOylation of Na V 1.5 channels was the underlying mechanism.…”
Section: Introductionmentioning
confidence: 98%
“…38,39 Since when SUMO has been discovered, 40 the importance related to this PTM has been investigated in eukaryotic cell lines, but only recently, it has been associated to control functions in differentiated organs like muscles and brain. 26,[41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, to initiate differentiation, medium was changed to CDM3, consisting of RPMI 1640 (Corning), 500 μg ml -1 Oryza sativa-derived recombinant human albumin (Oryzogen, Wuhan, China), and 213 μg ml -1 L-ascorbic acid 2-phosphate (Wako, Tokyo, Japan). For days 0-1, media was supplemented with 3 μM of the glycogen synthase kinase 3- inhibitor CHIR99021 (Biorbyt, San Francisco, USA) 21,22 and 10 ng ml -1 BMP4 (Peprotech, Hamburg, Germany). On day 1, media was changed to CDM3 and on d2 media was changed to CDM3 supplemented with 2 μM of the Wnt inhibitor Wnt-C59 (Biorbyt).…”
Section: Human Induced Pluripotent Stem Cell Culture and Cardiac Diffmentioning
confidence: 99%
“…For K v 7.1, it has also been shown that the A-kinase anchoring protein yotiao binds to helix D, leading to the recruitment of protein kinase A (PKA) and protein phosphatase 1, thereby forming a macromolecular complex important for regulating I Ks activity [20]. In addition to PKA-mediated phospho-rylation, ubiquitination and sumoylation have been reported to be important for regulation of K v 7.1 activity at the posttranslational level [21,22].…”
Section: Introductionmentioning
confidence: 99%